SEE & SAY: UTILIZING VISUALS TO STIMULATE NOVICE LEARNERS’ VERBALIZATION OF IDEAS IN THE TARGET LANGUAGE - Idek, Sirhajwan (PEOPLE: International Journal of Social Sciences, 2019)
The rise of information technology has transformed our way of communicating to each other as visuals have become as significant as verbal messages. Novice English language learners usually find it difficult to orally verbalize their understanding and ideas when they are given word-based texts. This research aimed to elicit oral responses from English language learners towards wordless still graphics by encouraging them to decode visuals through a specific strategy. The strategy is a set of hierarchical steps developed according to the model of understanding known as Structured Observed Learning Outcomes (SOLO) taxonomy with elements from several techniques including Visible Thinking Routine. The subjects were an intact class of 12 students of lower English language proficiency. Their responses towards a series of visuals were analyzed through concept maps. The findings revealed that they were able to orally verbalize their thoughts towards the visuals. This was an improvement from the initial reluctance and limited oral production they exhibited towards word-based texts. It is likely that wordless visuals might be as effective or probably more effective than words in eliciting ideas and language outputs from novice students. Hence, it is essential to consider viewing as the fifth language skill.